Determining factors that influence financial inclusion among SMEs: the case of Harare Metropolitan - Noor, Hanifa (Research of GSB, 2017)
Zimbabwe has been experiencing unprecedented levels of unemployment and high poverty. Against this backdrop, the growth of small- to- medium enterprises (SMEs) has been seen as a practical measure to help Zimbabwe's ailing economy address the complex macroeconomic challenges. However SMEs only receive 5% of total loans despite contributing 50% to GDP. This led to high levels of financial exclusion among the owners of SMEs, as banks cite credit risk as major challenge. Empirical evidence highlighted that 60% of the SMEs were financially excluded. This study explored the factors that influence financial inclusion of SMEs in Zimbabwe. This study analysed demand-side, supply-side and infrastructural constraints that inhibit financial inclusion. Demand-side factors of high transaction costs, financial illiteracy, and lack of confidence in the financial system and low levels of education resonated as issues among SMEs. On the supply side and infrastructural challenges: lack of widely accessible branches, information asymmetry, irrelevant financial products and service and high risk levels were the main deterrents within the financial sector. The population for the study was the Zimbabwean banking sector that comprised of 10 financial institutions and 50 SMEs that had been in operation from 2010 to 2015. The study collected primary data using semi-structured numerically coded questions and used descriptive statistical measure such as mean and standard deviation to analyse data. The results indicated that all demand-side, supply side and infrastructural factors were significantly related to the financial inclusion of SMEs. Evidence that their lack of confidence in the banking sector and prohibitive requirements including high bank charges were some of the key determinants negatively impacting financial inclusion. The smaller operators cited low incomes and the unavailability of savings as another deterrent. Evidence from financial institutions revealed absence of credit history, low-income levels, inadequate infrastructure, weak consumer protection regulations, and limited information on SME operations were inhibiting factors to financial exclusion. Based on the findings, the study recommended that government introduce financial education and introduce a policy that mandates financial institutions to provide relevant products and services to SMEs as an incentive to poverty reduction and economic development.